Contrasting Climate Sensitivity of Pinus cembra Tree-Ring Traits in the Carpathians - Știrbu, Marian-Ionuț; Roibu, Cătălin-Constantin; Carrer, Marco; Mursa, Andrei; Unterholzner, Lucrezia; Prendin, Angela Luisa (Frontiers in Plant Science, 2022)
High elevation ecosystems are one of the most sensitive to climate change. The analysis of growth and xylem structure of trees from marginal populations, especially the ones growing at the treeline, could provide early-warning signs to better understand species-specific responses to future climate conditions. In this study, we combined classical dendrochronology with wood density and anatomical measurements to investigate the climate sensitivity of Pinus cembra L., a typical European high-elevation tree species distributed in isolated patches in the Carpathians. Samples were collected from the Retezat Mountains, South-Western Romania. We analyzed ring-width (TRW), maximum density (MXD), xylem anatomical traits (cell number per ring (CNo), cell density (CD), conduit area (CA), and cell-wall thickness (CWT) time series, split into ring sectors and assessed the relationships with monthly and daily climate records over the last century (1901-2015). The analysis showed a strong dependency of TRW on CNo and MXD on CWT. Summer temperature positively correlated with MXD and CWT (monthly correlation (r) were 0.65 and 0.48 respectively) from the early- to late-wood but not TRW (r=0.22). CA positively correlated with water availability (r=0.37) and negatively correlated with temperature (r=-0.39). This study improves our general understanding of the climate-growth relationships of a European high-elevation tree species and the results could be considered for forecasting population dynamics on projected changes in climate.